Development of a mobile application as a facilitating tool in the teaching process in ophthalmology (Revista Contexto & Saúde, 2023)
The eyeball has functional differences and is very sensitive to aggressions, requiring special attention. One must pay attention to ophthalmologic emergencies, which represent a danger of ocular damage, sometimes irreversible, and must be treated as soon as possible. Thus, we sought to develop a mobile application as a quick guide, in which the doctor can select his diagnostic suspicion, ask questions, and see the appropriate treatment. This is a research of technological production for medical use, quantitative, descriptive, and transversal. During the development of the application, it was necessary to apply a questionnaire with professionals in the area, aiming to identify their level of contribution in diagnoses in ophthalmologic urgencies. The results show favorable responses to the application, focusing on ophthalmologic urgencies, with the presence of images and easy handling. The application presents itself as a teaching tool, as well as in diagnoses, prevention of damage, monitoring and control of complications in ophthalmologic emergencies.
Keywords: Eyeball; Ophthalmologic emergency; Digital guide; Mobile device; Suspicion diagnosis